Comparison and challenges in the implementation of Halal food laws in Malaysia, the Netherlands and United States of America - Hadi Akhbar Dahlan,; Norrakiah Abdullah Sani, (Penerbit Universiti Kebangsaan Malaysia, 2017)
The term “Halal Laws” in this paper relate to the laws of consumer protection in terms of Halal product. Halal laws are crucial, since it regulates an industry that is worth an estimated of USD 2.3 trillion, annually. The Halal laws in Malaysia are a national, legislated law. Meanwhile, the United States of America (USA) also have Halal laws, but it is legislated on a state level. Not all states recognise the Halal laws in the USA. Alternatively, the Netherlands do not have Halal laws or Halal related laws. Therefore, local Muslims depend on the integrity of local Halal certifier for Halal foods. This paper summarises the Halal laws differences in these 3 countries including Halal laws offenses and penalties. This paper also summarises the challenges of implementing the Halal laws in these three countries.